Alloplastic and Implant Materials for Bone Grafting: a Literature Review - U. F. Mukhametov; S. V. Lyulin; D. Y. Borzunov; I. F. Gareev; O. A. Beylerli; G. Yang (Креативная хирургия и онкология, 2021)
Bone reconstruction aft er trauma, infection, tumour or congenital genetic disorder is an important subject of modern medicine usually relying on bone graft ing materials. Autologous bone or autograft is still considered the “gold standard” most eff ective in bone defect reconstruction and osseous regeneration. Having the advantages of autograft ing, a series of issues remain related to a limited donor material, painful graft taking and the risk of putative complications (nonunions, graft rejection, infection, iatrogenic fractures, post-microsurgery arteriovenous shunt thrombosis, etc.). Th erefore, improved biomaterials are demanded to adequately meet the autograft criteria. Choosing optimal graft materials becomes relevant, aside to the rationale of selecting new surgical techniques. Th e osteoconductive and osteoinductive property evaluation in modern osteoplastic materials comprises a research avenue into optimal graft development for osseous correction in maxillofacial surgery, neurosurgery, traumatology and orthopaedics. Such biomaterials can be combined with alloplastic graft s to attain the required properties of osteoconduction, osteoinduction and osteogenesis. Th is analytic literature review focuses on current state-of-the-art in alloplastic graft ing that, in our opinion, grounds the progress of auto- and allograft innovative development.